INNOVATIVE POTENTIAL AND EFFICIENCY OF INDUSTRIAL ENTERPRISES IN UZBEKISTAN (International journal of artificial intelligence, 2025)
This article is devoted to the study of the innovative potential of industrial enterprises in Uzbekistan and its efficiency. The study analyzes the level of development of innovative processes in the country's industry, technological innovations and their economic efficiency. The article considers the factors that hinder the innovative activity of enterprises, as well as ways to eliminate them. Emphasizing the importance of innovations in the economy of Uzbekistan, the possibilities of increasing the competitiveness of the industry through the use of foreign experience and advanced technologies are considered.